2003
DOI: 10.1128/iai.71.8.4361-4367.2003
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Cellular Responses to IntraperitonealBrugia pahangiInfections in Normal and Immunodeficient Mice

Abstract: Filarial infections evoke exuberant inflammatory responses in the peritoneal cavities of immunocompetent mice. Clearance of infection appears to be dependent on complex interactions between B1 and B2 B lymphocytes, T cells, eosinophils, macrophages, and the products of these cells. In an earlier communication, we described the course of infection in normal immunocompetent mice. In this study, we utilize mice with well-characterized mutations that disable one or more effector components of adaptive immunity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 26 publications
(18 reference statements)
2
23
0
1
Order By: Relevance
“…Naive or day 14 Brugia-primed PECs were harvested from B6 wt mice and stained for CD11b, CD19, CD3, and IgM. Different cell populations were identified as previously described (2,12). IgM expression on the surface of various cell types is represented as an offset histogram overlay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Naive or day 14 Brugia-primed PECs were harvested from B6 wt mice and stained for CD11b, CD19, CD3, and IgM. Different cell populations were identified as previously described (2,12). IgM expression on the surface of various cell types is represented as an offset histogram overlay.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to understand host protective mechanisms, we have analyzed the kinetics of the host response to the i.p. injection of infective brugian larvae (1,2). We have shown that infection is followed by an exuberant inflammatory response, resulting in the accumulation of ϳ10 times as many leukocytes as are present in naive mice.…”
Section: Critical Role For Igm In Host Protection In Experimentalmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in a parasite closely related to B. malayi (B. pahangi), restimulation of splenocytes from infected mice expanded a population of CD25 worms transplanted into the peritoneal cavity live for 2-3 mo (34), in both cases inducing a highly polarized Th2 response (30,32,35). Moreover, infection of either stage into the peritoneal cavity results in a recruitment of well-characterized leukocyte populations (33), including suppressive alternatively activated macrophages (36). Within this timeframe, therefore, infection of mice with the human parasite sheds invaluable light on how the mammalian immune response reacts to, and may be manipulated by, filarial infections.…”
mentioning
confidence: 99%
“…Nós observamos que houve aumento de células positivas para os marcadores GR1, F4/80, CD3, CD4 e CD8 após a injeção de Ts2 ou Ts6. Estes são os marcadores de superfície comuns utilizados para caracterizar os neutrófilos (GR1), macrófagos (F4/80), linfócitos CD4 (CD3/CD4) e linfócitos CD8 (CD3/CD8), respectivamente (RAMALINGAM et al, 2003;PILLAI et al, 2009). …”
Section: Discussionunclassified